Cu-based Fe phosphate coating and its application in CO2 pipelines - Morks, Magdi F.; Fahim, Narges F.; Muster, Tim H.; Cole, Ivan S. (Surface and Coatings Technology, 2013)
Transportation of CO2 via steel pipelines from CO2 sources to storage wells will be required in the capture and storage (CCS) cycle. However if the CO2 stream contains contaminants, internal localized CO2 corrosion could occur. Further corrosion protection is also required to transport fluids in the hydrocarbon and chemical process industries if such fluids are acidified by in-situ speciation of carbonic acid (and other impurities). In this context, we report the feasibility of nanostructured Cu-based Fe phosphate coatings as a protection system for the interior surface of steel pipelines in acidified environments. Cu-based Fe phosphate coatings were deposited on mild steel surface via chemical conversion and electroless process. The idea behind phosphate protection is to build a thin dense phosphate layer (1.8 μm) that composed of Cu-nanoparticles (5–20 nm) attached to Fe phosphate plates of length 0.5–3 μm. The presence of nanostructured CuFe phosphate crystals and the suppression of the coating's pore formation are beneficial for enhancement the corrosion resistance of steel in chloride ions environment at pH 1 and 2. The passivation performance of CuFe phosphate coatings were examined by electrochemical studies namely: potentiodynamic polarization and electrochemical impedance spectroscopy. No Full Text